IMPLEMENTASI PELAYANAN PRIMA DI UNIT GUDANG KOPERASI KELUARGA BESAR SEMEN PADANG (KKSP) PT SEMEN PADANG (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This article discusses the implementation of excellent service in the Semen Padang Large Family Cooperative warehouse unit with a focus on the strategies, processes and results that have been achieved. By developing accounting information systems, developing organizational structures, employee development, and using technology, KKSP has improved the quality of services provided. Improving service quality has increased consumer confidence, sales and company image. Therefore, the implementation of excellent service at KKSP can be an example for other companies to improve the quality of services provided.